Stars and planets - Ridpath, Ian; Gallagher, Amie (DK Pub. New York, 2002)
Illustrates and describes each of the planets in the Solar System. With charts and diagrams, this title makes the often complex process of locating planets in the night sky simple. It includes a glossary that explains any scientific and technical terms used